Revolution Televised : Prime Time And The Struggle For Black Power - Acham, Christine (Book collections on Project MUSE., 2004)
In Revolution Televised, Christine Acham offers a complex reading of African American television history, finding within programs like Sanford and Son and Good Times opposition to dominant white constructions of African American identity. Revolution Televised deftly illustrates how black television artists operated within the constraints of the television industry to resist and ultimately shape the mass media's portrayal of African American life.